Cuba Calls: African American Tourism, Race, and the Cuban Revolution, 1959-1961. - Benson, Devyn Spence (Hispanic American Historical Review, 2013)
The article focuses on the history of race discrimination in Cuba between 1959 and 1961. The author examines the social conditions of Afro-Cubans in relation to the Cuban revolution, explores how African American tourism impacted race relations in Cuba, and analyzes programs sponsored by the Cuban National Tourist Institute (INIT), including an invitation for African American boxer Joe Louis to visit with Cuban president Fidel Castro.